Ecology : - Stiling, Peter D. (Prentice Hall, 1996)
This overview of evolutionary, behavioural, population, community and applied ecology covers the essentials required by beginning students. This edition has been thoroughly updated to reflect recent ideas, concepts and examples. It also features greater emphasis on applied ecology.